RELEVANSI PROBLEM-BASED LEARNING SEBAGAI BASIS FILOSOFIS DALAM PENGEMBANGAN BERPIKIR KRITIS ABAD 21 - Nur Hakimah; Nadhila; Rizka Nabila (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2025)
This study aims to analyze the effectiveness of implementing the Problem-Based Learning (PBL) model in enhancing students' critical thinking skills. PBL is a student-centered learning approach that emphasizes problem-solving as the core of the learning process. Through this method, students are encouraged to develop deeper analytical, evaluative, and synthetic skills. This study uses a quantitative method with an experimental design, where the experimental group uses the PBL model and the control group uses conventional teaching methods. Data were collected through critical thinking tests before and after the treatment. The analysis results show that the implementation of PBL significantly improves critical thinking skills compared to traditional learning methods. These findings reinforce that PBL not only helps students better understand the material but also fosters more logical, creative, and reflective thinking. Therefore, the use of the Problem-Based Learning model is recommended as an innovative strategy in education to equip students with the critical thinking skills essential for facing the challenges of the 21st century.